2015
DOI: 10.4103/2277-9175.151540
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Legionella spp. by a nested-PCR assay in air samples of a wastewater treatment plant and downwind distances in Isfahan

Abstract: Background:Wastewater contains a variety of pathogens and bio -aerosols generated during the wastewater treatment process, which could be a potential health risk for exposed individuals. This study was carried out to detect Legionella spp. in the bio -aerosols generated from different processes of a wastewater treatment plant (WWTP) in Isfahan, Iran, and the downwind distances.Materials and Methods:A total of 54 air samples were collected and analyzed for the presence of Legionella spp. by a nested- polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This bacterium can cause severe pneumonia (Legionellosis) when enough bacteria are inhaled and deposited in the alveoli of the lungs (Hamilton & Haas, 2016). Some studies have confirmed and quantified the presence of this bacteria in municipal (human) wastewater (Blatny et al., 2008; Medema et al., 2004; Mirzaee et al., 2015). It should be noted that this bacterium is from the water, not the waste, but its presence in wastewater that could be used for irrigation is cause for concern.…”
Section: Introductionmentioning
confidence: 89%
“…This bacterium can cause severe pneumonia (Legionellosis) when enough bacteria are inhaled and deposited in the alveoli of the lungs (Hamilton & Haas, 2016). Some studies have confirmed and quantified the presence of this bacteria in municipal (human) wastewater (Blatny et al., 2008; Medema et al., 2004; Mirzaee et al., 2015). It should be noted that this bacterium is from the water, not the waste, but its presence in wastewater that could be used for irrigation is cause for concern.…”
Section: Introductionmentioning
confidence: 89%
“…The formation of droplets and aerosolization of the pathogens from wastewater could be a major source of spread. There are examples of aerosolization of several pathogens from water such as Legionella, Cryptosporidium, Norovirus, and Hantavirus, resulting in ingestion or inhalation of the virus ( Brisebois et al 2018 ; Mirzaee et al 2015 ; Pascual et al 2003 ; Pillai 2002; Yazdanbakhsh et al 2020 ) ( Figure 5 ).
Figure 5 Distribution of human viruses in aerosols samples collected from sampling locations from three different sites of a WWTP in Canada.
…”
Section: Covid-19 and Watermentioning
confidence: 99%